2015
DOI: 10.1111/vsu.12326
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Postoperative Antimicrobial Use for Clean Orthopedic Implant Surgery in Dogs: A Prospective Randomized Study in 100 Consecutive Cases

Abstract: Administration of oral postoperative antimicrobials had a protective effect against development of SSI in clean orthopedic implant surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 23 publications
5
47
3
2
Order By: Relevance
“…We were unable to determine whether antibiotherapy had an effect in our population of heavier BW dogs because of the low number of infected cases. However, the correlation between BW and SSI is consistent with other studies . The SSI rate after TPLO in 208 dogs over 50 kg has been reported to reach 21.3%, with diagnosis of SSI in 24 of 40 (60%) dogs within 15 days and diagnosis of SSI in 6 of 40 (40%) dogs at least 2 weeks postoperatively .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We were unable to determine whether antibiotherapy had an effect in our population of heavier BW dogs because of the low number of infected cases. However, the correlation between BW and SSI is consistent with other studies . The SSI rate after TPLO in 208 dogs over 50 kg has been reported to reach 21.3%, with diagnosis of SSI in 24 of 40 (60%) dogs within 15 days and diagnosis of SSI in 6 of 40 (40%) dogs at least 2 weeks postoperatively .…”
Section: Discussionsupporting
confidence: 90%
“…Pratesi et al published a prospective randomized study of 100 consecutive clean orthopedic cases and found an association between total anesthesia time and SSI; however, the present study found no such correlation, nor did Fitzpatrick and Solano in their retrospective study of 1000 consecutive TPLO cases. There was no association between SSI and factors in Table beside those previously discussed.…”
Section: Discussioncontrasting
confidence: 87%
“…The infection rate of 2.83% in the present study is comparable to the SSI rates found in previous veterinary studies . Ten SSIs would have gone undetected by our facility had active surveillance not been performed.…”
Section: Discussionsupporting
confidence: 86%
“…We did not find a benefit with the use of postoperative antibiotics for the prevention of SSI after TTA. This is both in contrast to and in agreement with other reports of studies that evaluated the benefit of postoperative antibiotics at reducing the occurrence of SSI in proximal tibial osteotomy …”
Section: Discussionsupporting
confidence: 92%